2019
DOI: 10.7554/elife.46599
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II isoforms play distinct roles in adherens junction biogenesis

Abstract: Adherens junction (AJ) assembly under force is essential for many biological processes like epithelial monolayer bending, collective cell migration, cell extrusion and wound healing. The acto-myosin cytoskeleton acts as a major force-generator during the de novo formation and remodeling of AJ. Here, we investigated the role of non-muscle myosin II isoforms (NMIIA and NMIIB) in epithelial junction assembly. NMIIA and NMIIB differentially regulate biogenesis of AJ through association with distinct actin networks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 90 publications
10
59
0
Order By: Relevance
“…We observe reduced compaction when Myh9 is maternally deleted and slower compaction when Myh10 is deleted (Fig 1A-B). This is in agreement with cell culture studies, in which Myh9 knockdown reduces contact size whereas Myh10 knockdown does not [30,31]. This is also in agreement with previous studies using inhibitory drugs on the preimplantation embryo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observe reduced compaction when Myh9 is maternally deleted and slower compaction when Myh10 is deleted (Fig 1A-B). This is in agreement with cell culture studies, in which Myh9 knockdown reduces contact size whereas Myh10 knockdown does not [30,31]. This is also in agreement with previous studies using inhibitory drugs on the preimplantation embryo.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Myh9 plays a key role in setting the speed of furrow ingression during cytokinesis [27,28] and is essential to drive bleb retraction [29]. During cell-cell contact formation, Myh9 was found essential for cadherin adhesion molecule clustering and setting contact size while Myh10 would be involved in force transmissions across the junction and would influence contact rearrangements [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Two isoforms of non-muscle myosin II, NMIIA and NMIIB, localize to the epithelial AJC 7 . While both isoforms are necessary for the mechanical integrity of epithelial junctions, NMIIB is considered the dominant generator of force at AJC and is required for sustaining high tension along the cell-cell interface 7,38 . Therefore, we examined NMIIB localization in our knockout cell models.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in epithelial junction assembly, myosin IIA is parallel to the junction and provides mechanical force for the maintenance of adherens junction. Myosin IIB localizes at junctional membranes and organizes the junctional branched actin meshwork 18 . A recent study demonstrated that myosin IIA is dedicated to generating cortex tension for faster cleavage furrow ingression in cell division, while myosin IIB acts as a stabilizing motor by reducing cortex tension 19 .…”
Section: Introductionmentioning
confidence: 99%